Model Smart Beta dalam Menyusun Portofolio Optimal a Literature Review - Hana Tamara Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Theory of Capital Asset Pricing Model (CAPM) states that market risk (beta) can generate risk premium for investors. So investors only need to invest in a market portfolio or portfolio based on market capitalization weighting. Smart Beta portfolio is an index-based investment strategy that seeks to obtain superior risk-adjusted returns through transparent techniques and rules-based criteria based on specific factors or attributes that generate investment returns. Combining the Fama French Five Model, Variables Tracking Error and Active Share, this study proposes a Smart Beta model that will be selected from Issuers on the LQ 45 Index to 20 Issuers and compare which Return is better between IDX High Dividend Return 20 and Return from Issuer smart Beta portfolio results.